Adsorption of methylene blue on sodium alginate-flax seed ash beads: Isotherm, kinetic and thermodynamic studies - Isik, Birol; Ugraskan, Volkan (ELSEVIER, 2021)
In the present study, the adsorptive removal of methylene blue (MB) from wastewater was studied using the novel composite prepared by sodium alginate (SA) and flax seed ash (FS). The adsorption of MB was carried out using the composite beads consisting of different weight amounts of FS at different pH values and temperatures using different dye concentrations. The characterization studies of the composite beads were performed using Fourier-Transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), and Brunauer-Emmett-Teller and Barrett-Joyner-Hallenda (BET-BJH) analyses. BET and BJH surface area values of SA-FS adsorbent beads were found to be 45.01 m(2)/g and 14.35 m(2)/g, respectively. During the studies, it was determined that the adsorption percentage of MB reached the maximum with 90% at pH= 7 and 50 degrees C. Furthermore, Langmuir model fits well for the adsorption of MB using SA-FS with different FS ratios, SA, and FS adsorbents. The maximum adsorption capacity obtained from Langmuir model was found to be 333.3 mg/g for SA-FS-2 composite beads at pH = 7 and 50 degrees C. The adsorption kinetics were interpreted well by pseudo-second order model for SA, FS and SA-FS adsorbents. The calculated thermodynamic parameters indicated that MB adsorption by FS, SA, and SA-FS were spontaneous and an endothermic. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Sodium alginate; Flax seed ash; Adsorption; ACTIVATED CARBON; AQUEOUS-SOLUTION; DYE REMOVAL; CALCIUM ALGINATE; COMPOSITE BEADS; EFFICIENT ADSORBENT; AGRICULTURAL WASTE; BATCH ADSORPTION; HYDROGEL BEADS; SURFACE-AREA; Biochemistry & Molecular Biology; Chemistry; Polymer Science